STONE DISEASE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Gallstone disease (also cholelithiasis, cholelithiasis), cholelithiasis (Greek cholḗ - grass, bile, líthos - stone) is a gall bladder (cholecystolithiasis) and bile a disease characterized by the formation of stones (concrements) in the ducts (choledocholithiasis). Stones are formed as a result of bile pigments, cholesterol, some types of proteins, calcium salts, bile infection, its stagnation (stasis, stasis), lipid metabolism disorders. The disease can be accompanied by pain under the right rib, bilious colic, jaundice. Medical practice has shown that other methods of treating gallstones are ineffective, so surgical intervention is required. The disease can be complicated by cholecystitis, fistula formation, peritonitis.